Fatal giant cell myocarditis after resection of thymoma. - Glennon, P. E. (1996)
A case of fulminant, fatal myocarditis occurring 10 days after resection of a benign medullary thymoma is described. A rare association between thymoma and giant cell myocarditis is recognised, but fulminant presentation so soon after removal of thymoma has not previously been reported.